Organização e operacionalização da vigilância alimentar e nutricional: relatos de experiências de profissionais da atenção primária à saúde - Claro, Laura Virgili (2023)
The objective was to understand the practice of Food and Nutritional Surveillance (VAN), with regard to its organization and operation, according to the perspective of Primary Health Care (APS) professionals from municipalities in Rio Grande do Sul State, Brazil. This is a descriptive and exploratory research, with a quantitative and qualitative character. The research included the creation of an Observatory of Food and Nutrition Surveillance (OVAN) for the municipalities of RS, after a public call notice was launched on the OVAN website, for sending reports of experiences by APS professionals from municipalities in Rio Grande do Sul, which involved the organization and operation of the Food and Nutrition Surveillance, having as a guiding axis the Care Management and Production Cycle. The experience reports sent were submitted to a systematization of experiences and a content analysis, respectively. The sample consisted of 42 reports of experiences developed in 24 municipalities that indicated actions involving the concentration on the collection of anthropometric data, registration in the information systems made available by the Unified Health System (SUS), actions aimed at students within the scope of the school space. In their entirety, the nutritionists were responsible for carrying out the reports, with greater collaboration from the Community Health Agents in relation to other health professionals for the development of actions, and intersectoral articulation with the education departments and the Health at School, Growing Healthy and Protect Programs (Programas Saúde na Escola, Crescer Saudável e Proteja). The research showed that given the importance of Food and Nutrition Surveillance in Primary Health Care, difficulties are identified for its implementation, identified as historical barriers, persisting in models that centralize the conduction of actions in the nutritionist and in the collection of anthropometric data, with a focus on in children and in programs that condition the financial transfer from the achievement of goals, distancing itself from the realization of the vigilance attitude.